Characterization of teaching work under burnout syndrome - Monreal-Torres, Johanaly (2025)
The text presents a literature review on burnout syndrome in teachers as a manifestation of chronic stress, particularly in the context of virtual education during the COVID-19 pandemic. To this end, an exploratory study was conducted through a review of current scientific literature. Burnout was characterized in terms of its main symptoms—physical and emotional exhaustion, depersonalization, and reduced personal accomplishment—as well as the risk factors associated with the new demands of the educational environment. Furthermore, the effects of the forced virtualization of teaching were examined, along with prevention strategies and resilience factors. The findings highlight the importance of implementing effective institutional support and stress management measures to mitigate the negative effects of burnout and strengthen teacher resilience as a mechanism for coping with adversity and promoting professional well-being.